Pelvic floor muscle training improves erectile dysfunction and premature ejaculation: a systematic review. Issue 2 (June 2019) - Myers, Christopher; Smith, Moira
Abstract: Background: Erectile dysfunction (ED) and premature ejaculation (PE) often have underlying musculoskeletal abnormalities. Despite this, traditional management has focused on pharmaceutical prescription. Objective: To investigate the efficacy of pelvic floor muscle training in treating ED and PE. Data sources: A computerized literature search of CINAHL ®, Cochrane, InFormit, Ovid Medline, Pedro, and Scopus (from inception until January 2018) was conducted of type of dysfunction and intervention. Secondary search strategies included Medical Subject Headings expansion, hand searching of conference abstracts, key authors, reference lists and forward citation searching via Web of Science. Study selection: All studies where participants were males greater than 18 years with ED or PE, with no history of neurological injury or previous major urological surgery were included. Study appraisal: Two independent reviewers assessed methodological quality using the Crowe Critical Appraisal Tool. Disagreements between reviewers were resolved by consensus. Results: Ten trials were included for review. Among the measures of ED, all trials showed comparative improvement and cure rates in response to treatment. Within PE outcomes, the majority of trials showed comparative improvement rates, with a greater range in overall cure rates in response to treatment. Training protocols varied significantly in overall therapist contact, concurrent interventions, intervention length, training frequency and intensity. Limitations: The included studies were of low to moderate methodological quality with discrepancies in reporting. Study heterogeneity was not conducive to data pooling. Conclusion: Pelvic floor muscle training appears effective in treating ED and PE; however, no optimal training protocol has been identified. Systematic Review Registration Number: PROSPERO CRD42016047261.